2005
DOI: 10.1210/en.2004-0946
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor Is Released from Pituitary Folliculo-Stellate-Like Cells by Endotoxin and Dexamethasone and Attenuates the Steroid-Induced Inhibition of Interleukin 6 Release

Abstract: Macrophage migration inhibitory factor (MIF) is a proinflammatory cytokine produced by peripheral immune cells and also by endocrine cells in the anterior pituitary gland. MIF exerts its proinflammatory actions in the host-defense system by blocking the inhibitory effects of glucocorticoids on the release of other proinflammatory cytokines (e.g. IL-1, IL-6, TNFalpha). Reports that pituitary folliculo-stellate (FS) cells share many characteristics with immune cells led us to propose that these cells may serve a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…Very recently, Tierney et al (14) found immunoreactivity to the proinflammatory cytokine MIF in part of the S-100…”
Section: Embryological Origin Of Fs Cells and Functional Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Very recently, Tierney et al (14) found immunoreactivity to the proinflammatory cytokine MIF in part of the S-100…”
Section: Embryological Origin Of Fs Cells and Functional Implicationsmentioning
confidence: 99%
“…A still growing list includes S-100 (54), bFGF (9), VEGF and follistatin (10, 11), IL-6 (13, 53, 81), LIF (12), MIF (14) and IL-10 (86). FS cells were indicated as the most plausible source of (most of) the latter growth factors and cytokines, although, for instance in human pituitary adenomas, evidence was provided that S-100 þ FS cells were not the major source of Il-6 (87).…”
Section: New Perspectives In Fs Cell Physiologymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to modulating hormone secretion in the anterior lobe [11,12], these cells seem to play a central role in co-ordinating the interplay between the immune and endocrine systems [13]. The recent demonstration of macrophage migration inhibitory factor expression and secretion in cultured FS cells [14], and its modification by glucocorticoids, supports this contention. We have previously shown that adenosine can stimulate IL-6 production in cultured FS cells, an effect mediated via the A2b adenosine receptor subclass and involving activation of p38 MAP kinase [15,16].…”
Section: Introductionmentioning
confidence: 99%